Faktor Hidro-Oseanografi Terhadap Distribusi Air Tawar Bersuhu Rendah Dekat Pantai Sekitar Lokasi Keluaran Air Tanah Lepas Pantai (KALP) di Perairan Lombok Utara, Indonesia - Ulung Jantama Wisha; Gunardi Kusumah, (OLDI (Oseanologi dan Limnologi di Indonesia), 2026)
The Influence of Hydro-Oceanography Factors on the Distribution of Near-shore Low-Temperature Freshwater around Submarine Groundwater Discharge (SGD) Area in the North Lombok Waters, Indonesia. North Lombok coast has lot of resources of Submarine Groundwater Discharge (SGD). The biggest discharge appeared in the Krakas Beach where cold groundwater discharge many spots might trigger anomalies in the ambient water temperature. This study was aimed at determining the distribution of the cold groundwater discharge. A field survey was conducted on March 23th -26th, 2016. Flow model and statistical analysis were employed to determine the transport pattern of temperature anomalies. Vertically, the current direction is in accordance with Ekman spiral that triggers the vertical cold groundwater distribution. The current speed during the displacement toward high tide ranges 0-0.15 cm/s which predominantly moves south-westward. During low tide, tidal current was predominantly north-eastward moving at 0-0.3 cm/s. Temperature variation around the SGD spot fluctuated following sea surface surface elevation dynamics in which these two parameters has a correlation value of 63%.